2013
DOI: 10.1002/hed.23294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of indeterminate pulmonary nodules in patients with locally advanced head and neck squamous cell carcinoma

Abstract: IPNs at staging in patients with HNSCC do not affect prognosis and should neither influence initial treatment planning nor the frequency of posttreatment surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In the present study, 3.8% of initially indeterminate index nodules were subsequently demonstrated to represent malignant disease. Our results are similar to our previous finding of a 6% malignancy rate in pulmonary nodules but are significantly lower than multiple previous reports 12–15 . One reason for the discrepancies in older papers and our work along with our contemporaries could be the improvements made in CT imaging which may allow for smaller pulmonary nodules to be detected.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, 3.8% of initially indeterminate index nodules were subsequently demonstrated to represent malignant disease. Our results are similar to our previous finding of a 6% malignancy rate in pulmonary nodules but are significantly lower than multiple previous reports 12–15 . One reason for the discrepancies in older papers and our work along with our contemporaries could be the improvements made in CT imaging which may allow for smaller pulmonary nodules to be detected.…”
Section: Discussionsupporting
confidence: 86%
“…P16 status may be an important consideration when determining the risk of a small pulmonary nodule in HNC in the context of small pulmonary nodules and the major recommendation from this study is that the predictive power of negative p16 status should be assessed on a larger scale to assess its importance when determining the risk of small pulmonary nodules in HNC. Volume n = 105 (mm 3 ) 25 20 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) .594…”
Section: Discussionmentioning
confidence: 99%
“…This supported previous evidence that those patients with recurrent head and neck cancers are more likely to have malignant involvement of the lungs. 24 In 2013, Alford et al 25 reported on patients with higher grade primary head and neck cancers, with initially indeterminate lung nodules who were more likely to have lung metastases. In 2014, Fukuhara et al 26 investigated lung nodules in 332 patients with head and neck cancer and demonstrated that having pulmonary nodules on an initial CT scan increased the risk of developing lung metastases.…”
mentioning
confidence: 99%